2019
DOI: 10.1155/2019/6357171
|View full text |Cite
|
Sign up to set email alerts
|

Cobb Angle Measurement of Spine from X-Ray Images Using Convolutional Neural Network

Abstract: Scoliosis is a common spinal condition where the spine curves to the side and thus deforms the spine. Curvature estimation provides a powerful index to evaluate the deformation severity of scoliosis. In current clinical diagnosis, the standard curvature estimation method for assessing the curvature quantitatively is done by measuring the Cobb angle, which is the angle between two lines, drawn perpendicular to the upper endplate of the uppermost vertebra involved and the lower endplate of the lowest vertebra in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
121
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(180 citation statements)
references
References 29 publications
(38 reference statements)
3
121
0
5
Order By: Relevance
“…В качестве одной из ключевых задач была выбрана подготовка данных, и значительное внимание уделено созданию датасета рентгенограмм для обучения нейросети. Если большинство результатов исследований базировалось на анализе 14-49 рентгенограмм, то мы провели обучение сети на 300 цифровых рентгенограммах позвоночника больных идиопатическим сколиозом, предварительно расчерченных врачомрентгенологом [9][10][11][12][13][14]25]. Сопоставимый объем исследований прослежен только в работах J. Wang et al и Y. Pan et al [11,13].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…В качестве одной из ключевых задач была выбрана подготовка данных, и значительное внимание уделено созданию датасета рентгенограмм для обучения нейросети. Если большинство результатов исследований базировалось на анализе 14-49 рентгенограмм, то мы провели обучение сети на 300 цифровых рентгенограммах позвоночника больных идиопатическим сколиозом, предварительно расчерченных врачомрентгенологом [9][10][11][12][13][14]25]. Сопоставимый объем исследований прослежен только в работах J. Wang et al и Y. Pan et al [11,13].…”
Section: Discussionunclassified
“…Анализ литературы показал, что за последние 10 лет выполнено большое количество работ, посвященных цифровым программным решениям при вычислении величины угла Кобба на рентгенограммах, причем увеличение количества таких исследований в первую очередь обусловлено развитием цифровой рентгенографии [9][10][11][12][13]. В то же время предлагаемые решения фактически являются либо полуавтоматическими в ситуациях, когда врач определяет начальный и конечный позвонки дуг, либо полностью ручными, но с использованием программного обеспечения, позволяющего увеличить изображение и более точно провести касательные к проекции тела позвонка [14].…”
unclassified
See 1 more Smart Citation
“…However, these studies need more clarification. 19 It should be noted that previous recommendations showed that it should be a routine to screen children for scoliosis, because there is a large number of school children suffering from adolescent idiopathic scoliosis (AIS). However, the specific methods should be used because of the controversy shown in the context of school screening programs.…”
Section: Spinalmeter Methods For the Determination Of Postural Status mentioning
confidence: 99%
“…Scoliosis is usually considered severe when the spinal curve measured with the Cobb method exceeds 40° to 50°. Progressed scoliosis requires surgery, mostly posterior corrective spinal fusion surgery in adolescence [6,7].…”
mentioning
confidence: 99%